Literasi Matematika Ditinjau dari Self-efficacy pada Materi Barisan dan Deret Aritmetika - Rosdiana, Anisa; Kartono, Kartono; Kharisudin, Iqbal (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2023)
Until now, many students still perceive mathematics as a subject filled with calculations. This causes them to be unwilling to learn mathematics because counting and thinking are not considered interesting activities. This situation is also evident among students at SMA Ma’arif Karangmoncol Purbalingga. This research aims to determine the mathematical literacy of students at SMA Ma’arif Karangmoncol Purbalingga in the material of arithmetic sequences and series, considering their self-efficacy. This qualitative descriptive research involves 6 students selected from an initial sample of 30 students, chosen based on inclusion criteria. The researcher utilized three instruments for data collection: a self-efficacy questionnaire, a mathematics literacy test, and interviews. The analysis technique employed is triangulation, where the researcher cross-examines the results of the literacy test with the interview findings. Research findings 1) Students with high self-efficacy demonstrate high mathematical literacy, 2) Students with moderate self-efficacy exhibit moderate mathematical literacy, and 3) Students with low self-efficacy display low mathematical literacy. Based on the research results, the researcher concludes that the higher the students' self-efficacy, the higher their mathematical literacy. This study serves as a noteworthy consideration for teachers, highlighting that self-efficacy is one of the affective skills that students should possess.